TACI haploinsufficiency protects against BAFF‐driven humoral autoimmunity in mice. Issue 9 (27th June 2021) - Jacobs, Holly M.; Arkatkar, Tanvi; Du, Samuel W.; Scharping, Nicole E.; Woods, Jonathan; Li, Quan‐Zhen; Hudkins, Kelly L.; Alpers, Charles E.; Rawlings, David J.; Jackson, Shaun W.
Abstract: Polymorphisms in TACI, a BAFF family cytokine receptor, are linked to diverse human immune disorders including common variable immunodeficiency (CVID) and systemic lupus erythematosus (SLE). Functional studies of individual variants show modest impacts on surface TACI expression and/or downstream signal transduction, indicating that relatively subtle variation in TACI activity can impact human B‐cell biology. However, significant complexity underlies TACI biology, including both positive and negative regulation of physiologic and pathogenic B‐cell responses. To model these contradictory events, we compared the functional impact of TACI deletion on separate models of murine SLE driven by T cell‐independent and ‐dependent breaks in B‐cell tolerance. First, we studied whether reduced surface TACI expression was sufficient to protect against progressive BAFF‐mediated systemic autoimmunity. Strikingly, despite a relatively modest impact on surface TACI levels, TACI haploinsufficiency markedly reduced pathogenic RNA‐associated autoantibody titers and conferred long‐term protection from BAFF‐driven lupus nephritis. In contrast, B cell‐intrinsic TACI deletion exerted a limited impact of autoantibody generation in murine lupus characterized by spontaneous germinal center formation and T cell‐dependent humoral autoimmunity. Together, these combined data provide new insights into TACI biology and highlight how TACI signals must be tightly regulated during protective and pathogenic B‐cell responses. Abstract : Both extra‐follicular (EF) and germinal center (GC)‐dependent B‐cell activation pathways contribute to the generation of autoantibody‐producing plasma cells in systemic lupus erythematosus (SLE). We show that, whereas B‐cell TACI expression is redundant for autoimmune GC formation, heterozygous TACI deletion protects against BAFF‐driven murine SLE. These data indicate that a threshold of TACI signals is required to drive breaks in immune tolerance and promote the EF activation of autoreactive B cells.